THE EFFECTS OF SERVICE QUALITY, CUSTOMER PERCEIVED VALUE, AND CUSTOMER SATISFACTION TOWARDS CUSTOMER LOYALTY OF DAMRI TOUR BUS - Wachyuni, Suci Sandi (Journal of Business on Hospitality and Tourism, 2019)
Based on the data from Transportation Department of Indonesia, commonly total of tourist bus company and total unit of tour bus continues to increase every year. The increasing number of competitors will affect customers looking away easily from one service provider to another. Then, DAMRI as one of the providers, has to make efforts for maintaining and increasing customer’s loyalty. The purpose of this study to determine the effect of service quality, customer perceived value, and customer satisfaction towards customer loyalty of DAMRI Tourist Bus.This research is a quantitative research. Sampling technique is non Probability Sampling, purposive sampling. Data collection is done through interview and questionnaires. Statistical analysis techniques is done through regression analysis and hypothesis testing t test and F test (SPSS 20.0). The results being obtained: service quality (X1) and customer perceived value (X2) significantly influence customer loyalty (Y). In other hand, customer satisfaction (X3) does not significantly influence customer loyalty (Y); But X1, X2, and X3 simultanously influence Y. The manager is advised to continously make efforts in order to improve customer loyalty. Further research is needed to identify the factors that have more influence over customer loyalty of DAMRI Tourist Bus.